Revisiting the anatomy of inferior extensor retinaculum of foot and ankle, a study based on fifty embalmed adult cadaveric lower extremities - M. Praveen Shenoy; Mangala M. Pai; B.V. Murlimanju; Rajanigandha Vadgaonkar; Latha V. Prabhu; M.D. Prameela (Translational Research in Anatomy)
Background: The facial condensation of deep fascia form retinacula, Superior and Inferior, with a primary function to hold the extensor tendons of the foot in position. The morphology of inferior extensor retinaculum (IER) is clinically important in the tendon rupture repair and foot drop surgeries. The anatomy of ankle and foot IER is not much investigated and this prompted us to conceptualize this study to investigate the morphology and morphological variants of IER. Methods: This descriptive, cross-sectional institutional based study included 50 dorsa of feet from the 25 embalmed adult cadavers. Results: The present study observed that, the anatomy of IER is complex wherein multiple septa of varied thickness arise from its undersurface from both the stem and limbs, defining its compartments. Five well defined compartments existed, which lodged the extensor tendons. The third compartment was deep and overlapped by the extensor digitorum longus tendons. Fourth compartment was well defined and lodged the extensor digitorum longus and peroneus tertius tendons, separated by an ill-defined septum. However, in 6 specimens (12 %), the peroneus tertius traversed the fifth compartment, which otherwise did not have any contents. Some morphological variants of the tendons were also noted as they passed beneath the IER. Conclusion: Our study is novel in determining the compartment format, deeper connections of IER, and relations with deeper structures along with the anatomical variations, which are clinically important in ankle arthroscopy, tendinoscopy, tendon repairs and foot drop stabilization surgeries.